2014
DOI: 10.3109/07435800.2014.987398
|View full text |Cite
|
Sign up to set email alerts
|

Association between red blood cell distribution width and polycystic ovary syndrome

Abstract: RDW levels were higher in women with PCOS, and high-RDW levels were independently associated with PCOS. This link in between RDW and PCOS may be due to an underlying chronic inflammation in subjects with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
2
7
4
Order By: Relevance
“… 4 Unlike our findings, a significantly higher RDW (another inflammatory marker) was reported in women in the PCOS group compared with the control group. 4 …”
Section: Discussioncontrasting
confidence: 99%
“… 4 Unlike our findings, a significantly higher RDW (another inflammatory marker) was reported in women in the PCOS group compared with the control group. 4 …”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, a number of studies have reported a correlation in decreased MCV with inflammation markers in patients with inflammatory bowel disease [28,29]. The findings of this study showed a direct association between WC and RDW, which is in line with previous studies that reported significantly higher mean platelet volume and RDW in patients with adiposity related MetS compared to those without MetS or positively correlated with high-sensitive CRP, HOMA insulin resistance and BMI [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…In the past several years, RDW has received the attention in the field of inflammation inasmuch as it was associated with the presences and outcomes in patients with polycystic ovary syndrome, ankylosing spondylitis, myocardial infarction, acute pancreatitis-associated lung injury, and spontaneous echo contrast. 4 8 Magnetic resonance imaging (MRI), as a expensive checking method, is clinically a valuation methodology of brain or spinal cord disease activity of MS. 9 It has been previously observed that the pathogenesis of MS is associated with inflammatory factors, and found that pro-inflammatory cytokines increase in patients with MS such as tumor necrosis factor (TNF) and interleukin-1β (IL-1β). 10 11 It is then noteworthy that loss of polyunsaturated fatty acids from plasma and blood cell membranes is observed in patients with MS, 12 which contributes to the variation of erythrocyte deformability.…”
Section: Introductionmentioning
confidence: 99%